Obtaining and confirming consent. (2nd December 2019) - Symon, Andrew
Abstract : The question of how practitioners provide information and verify that a woman understands the issues and consents to a procedure was raised in the High Court. Andrew Symon reports on Mordel v Royal Berkshire NHS